Updated recommendations for the treatment of light-chain amyloidosis from the Swiss Amyloidosis Network - Rieger, Max J.; Flammer, Andreas J.; Gerull, Sabine; Pabst, Thomas; Auner, Holger W.; Samii, Kaveh; Hitz, Felicitas; Mey, Ulrich; Ballova, Veronika; Battegay, Raphael; Melli, Giorgia; Benz, Dominik; et al. (Swiss medical weekly, 2025)
Since the publication of the first Swiss recommendations on systemic light-chain amyloidosis in 2020, treatment strategies have evolved. As a result of the third joint meeting of the Swiss Amyloidosis Network, a multidisciplinary and multicentre Swiss clinical consortium, in 2024, recommendations for the treatment of light-chain amyloidosis were updated. They discuss the role of the new standard first-line protocol Daratumumab, Cyclophosphamide, Bortezomib, Dexamethasone (Dara-CyBorD), the timing and indication of high-dose treatment and potential second-line strategies as well as emerging treatment options, with a special focus on multidisciplinary supportive care measures. The update represents a synopsis of current evidence and expert consensus and intends to provide general treatment guidance tailored to the Swiss healthcare system. Nonetheless, treatment decisions should always be personalised and involve a multidisciplinary approach. This update replaces the previous “therapeutic recommendations” while the previous “diagnostic recommendations” remain valid.